Elimination of Negative Impacts of Steel Scrap as a Charge Component during the Production of Synthetic Cast Iron - Peter Futas; Alena Pribulova; Jozef Petrik; Marcela Malindzakova; Andrea Rosova; Beata Grabowska (Communications - Scientific letters of the University of Zilina, 2016)
The article presents the research results of omitting the steel scrap component from the production process of synthetic gray cast iron. The quality of synthetic iron produced in electric induction furnaces (EIF) is influenced by numerous factors. Its characteristic attributes are high values of mechanical properties (Rm, HB), but also its tendency to form chill out and shrinkages, foundry stress and sensitivity to hardness change at different casting wall thicknesses. Possibilities of offsetting and eliminating such negative effects were tested by introducing metallurgical countermeasures based on the properties of flake graphite alloys.